1990
DOI: 10.1210/endo-126-5-2417
|View full text |Cite
|
Sign up to set email alerts
|

The Ontogeny of the Rabbit Brain Glucose Transporter*

Abstract: We investigated the presence of three specific types of glucose transporters (GT) within the rabbit central nervous system during various developmental stages. Employing the Hep G2/brain-type insulin-insensitive and the insulin-responsive (IRGT; adipocyte/skeletal muscle type) GT antibody and cDNA, we studied protein and mRNA within the whole brain (25-, 27-, and 30-day-old fetus; 1-, 5-, 10-day-old neonate; and adult), using cultured neuronal and glial cells, by Western and Northern blot analysis. Similarly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…As expected, the insulin-sensitive transporter, GLUT4, was not detected in homogenates of whole brain (Sadiq et al 1990). GLUT2, the low-affinity transporter of the liver and pancreas, also has not been found in whole brain (Thorens et al 1988).…”
Section: I S T R I B U T I O N Of G L U C O S E T R a N S P O R T Esupporting
confidence: 75%
“…As expected, the insulin-sensitive transporter, GLUT4, was not detected in homogenates of whole brain (Sadiq et al 1990). GLUT2, the low-affinity transporter of the liver and pancreas, also has not been found in whole brain (Thorens et al 1988).…”
Section: I S T R I B U T I O N Of G L U C O S E T R a N S P O R T Esupporting
confidence: 75%
“…As in cattle (present study), GLUT1 expression has also been shown to be maximal in early foetal life and to decrease steadily throughout gestation in the heart and skeletal muscle of the chicken [33]. Some species-specific regulation has, however, been demonstrated: GLUT1 expression at both the protein and mRNA levels is indeed shown to decrease after birth in the rat heart [11] and in the brain, lung, liver and kidney of rodents [34][35][36], whereas the GLUT1 level does not change in the skeletal muscle and adipose tissue of Holstein male calves from birth to 12 months of age [37]. Our study confirmed that birth is not associated with major and statistically significant changes in GLUT1 expression in either heart or adipose tissue of cattle.…”
Section: Ontogenesis Of Glucose Transporterssupporting
confidence: 67%
“…Glut 3 has been found in small amounts in fetal and newborn rabbit brain (8). Our data suggest that little Glut 3 (as measured by the mouse cDNA probe) is expressed in the fetal rat brain and even less is expressed in lung.…”
Section: Brain Lungmentioning
confidence: 57%
“…cDNA encoding a glucose transporter have been cloned from both rat brain and human hepatoma (Hep G2) cell libraries (6,7). This glucose transporter has been termed Glut 1 and is present in most fetal tissues including brain (8,9). Glut 3, originally cloned from human fetal skeletal muscle, has been found in small quantities in fetal rabbit brain (9).…”
mentioning
confidence: 99%